Modes of a Plasma-Filled Waveguide Determined by a Numerical hp Method (Communications in Computational Physics, 2018)
We present the application of the recent physics-conforming COOL method[2, 4] to the eigenvalue problem of a cylindrical waveguide filled with unmagnetizedplasma. Using the Fourier transform only along the waveguide and not in poloidal direction, this is a relevant test case for a numerical discretization method in two dimensions (radial and poloidal). Analytically, the frequency spectrum consists of discreteelectromagnetic parts and, depending on the electron density profile of the plasma, ofinfinitely degenerate and/or continuous, essentially electrostatic parts. If the plasmais absent, the latter reduces to the infinitely degenerate zero eigenvalue of electrostatics. A good discretization method for the Maxwell equations must reproduce theseproperties. It is shown here that the COOL method meets this demand properly andto very high precision.